Lower Little Blue Watershed Assessment: Preliminary Report - Nejadhashemi, A. P.; Smith, C.M.; Mankin, K.R.; Wilson, R.M.; Brown, S.P.; Leatherman, J.C. (My University, 2009)
A preliminary assessment of the Lower Little Blue Watershed in northeast Kansas.
EP141_2009-02
Keywords: EP141; Environment and Natural Resources; EP